Allocation rules for a commonly owned technology: the average cost lower bound. - Maniquet, François (Journal of Economic Theory, 1996)
The writer examines the compatibilities and incompatibilities between the average cost lower bound and other ethically attractive equity requirements that need to be satisfied when studying equity in economic environments. He defines the average cost lower bound as the requirement that every agent must be as well off at a selected allocation as at the average cost equilibrium that all agents prefer. He combines the new lower bound with properties such as technological monotonicity or contraction independence to characterize Mas-Colell's constant returns equivalent allocation rule.